A diagnostic score for eosinophilic granulomatosis with polyangiitis among eosinophilic disorders - Hideyuki Takahashi; Toshihiko Komai; Keigo Setoguchi; Hirofumi Shoda; Keishi Fujio (Allergology International, 2023)
Background: Eosinophilic granulomatosis with polyangiitis (EGPA) is a form of systemic vasculitis with eosinophilic inflammation. However, existing classification criteria are all designed to classify EGPA among vasculitis and there is no established method distinguishing EGPA from other eosinophilic disorders. The aim of the present study was to propose a scoring system to differentiate EGPA among eosinophilic disorders. Methods: Non-supervised hierarchical clustering using Ward's method and principal component analysis (PCA) were performed for 19 clinical parameters of 58 patients with eosinophilia-related diseases at a tertiary university hospital. The newly proposed scoring system was externally validated in 40 patients at another tertiary institution. Results: Two distinct clusters were identified, and clinical features including peripheral neuropathy, asthma, skin involvement, lung involvement, rheumatoid factor (RF) positivity, myeloperoxidase (MPO)–anti-neutrophil cytoplasmic antibody (ANCA) positivity, IgE elevation, C-reactive protein (CRP) elevation, and vasculitis pathological findings were predominantly observed in one of these clusters (p < 0.05). Ten features defining the cluster with a high rate of vasculitis were weighted by PCA to create the E-CASE (EGPA classification among systemic eosinophilia) scoring system, on a 16-point scale. Based on the distribution of scores in the primary cohort, we defined an E-CASE score ≥12 as positive, ≤ 8 as negative, and 9–11 as undeterminable. The sensitivity and specificity of the E-CASE score in the validation cohort were 93.3% and 100%, respectively. Conclusions: We developed and verified a novel scoring system for differentiating EGPA from other types of eosinophilic disorders.